Multimedia Kuronthogai / Mohan Sellappan - Mohan, Sellappan (2000)
Project Multimedia Kuronthogai is a Final Year Project (Thesis) offered by the Faculty of Computer Science & Information Technology. This project was divided into Thesis I and Thesis II and supervised by my project supervisor Assoc. Prof. Dr. N.Selvanathan. The moderator for this project is Cik Hannyzzura Affal. Kuronthogai is a one of the Tamil anthologies. It contains 401 poems. The theme of these poems is love and the verse are of the five lands (tinais) in appropriate time. Most of the Tamil literatures are in the form of a book. Only few of them are in Multimedia environment. It is important to bring the Tamil literatures in Multimedia environment. The main objective of this project is to bring the Kuronthogai into a Multimedia environment. This Multimedia application will be a tool that will provide almost full assistance to the Tamil literature researcher. Chapter 1 of this report covered the general view of this project. This chapter covers the objective of this project, how this project was planned, the project scheduling, expected out come and the system requirement. Chapter 2 covers literature review . It contains a brief history of the Tamil literatures and how the poem in Kuronthogai were divided. The tools used for developing this application are Macromedia Director 6.0, Datagrip, Microsoft Access 7.0 and Murasu Anjal Tamil word processor. Chapter 3 covers the methodology of this application. The database design and system design were described in this chapter. Chapter 4 covers implementation, chapter 5 covers testing and chapter 6 covers evaluation.